Evaluation of the impact of blood donation on tissue perfusion and sublingual microcirculation in dogs: A pilot study. (20th December 2022) - Magnin, Mathieu; Oriel, Justine; Combet-Curt, Julie; Salama, Johanna; Allaouchiche, Bernard; Bonnet-Garin, Jeanne-Marie; Junot, Stéphane; Pouzot-Nevoret, Céline
Abstract: The objective was to assess the feasibility of the sublingual microcirculation evaluation in dogs by using Sidestream Dark Field (SDF) imaging device and to evaluate the impact of blood donation on sublingual microcirculation and tissue perfusion. Before and after blood sampling, macrocirculatory parameters and tissue perfusion parameters were collected. After quality assessment, four videos per individual and per period were retained for analysis. Data were presented as median (1st quartile – 3rd quartile). The evaluation of the sublingual microcirculation with SDF was feasible in sedated dogs: good quality videos could be recorded in 10/12 dogs (83%). The median blood donation volume was 14 mL/kg (13–15). A significant association between the volume of blood collected and the increase in heart rate was observed: for each milliliter of blood drawn, heart rate increased by 1 bpm (CI95% = [0.2, 2], P  = 0.03). Blood collection was associated with a significant increase of shock index (estimate = 0.17, CI95% = [0.02, 0.32], P  = 0.04). After blood donation, lactate concentration significantly decreased (before: 2.1 (1.7–2.8), after: 1.1 (0.8–1.7) mmol/l, P  = 0.009). No significant variation of the microcirculatory parameters was observed. In conclusion, sublingual evaluation of the microcirculation with SDF technology is feasible in dogs. In the present condition, blood donation did not significantly alter microcirculation. These results need to be confirmed in a larger population. Highlights: Evaluation of sublingual microcirculation with videomicroscopy is feasible in dogs. Blood donation was not associated with significant hypoperfusion. Blood donation was not associated with significant sublingual microcirculation disorders.